2016
DOI: 10.3389/fmicb.2016.01948
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Antibacterial Action of Quinoxaline 1,4-di-N-oxides against Clostridium perfringens and Brachyspira hyodysenteriae

Abstract: Quinoxaline 1,4-di-N-oxides (QdNOs) are a class of bioreductive compounds, however, their antibacterial mechanisms are still unclarified. The aim of this study was to assess the ability of two representative QdNO drugs, cyadox (CYA) and olaquindox (OLA), to produce reactive oxide species (ROS) in Gram-positive anaerobe Clostridium perfringens CVCC1125 and Gram-negative anaerobe Brachyspira hyodysenteriae B204. In addition, the effects of QdNOs on the integrity of bacterial cell walls and membranes as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…As many studies suggested, QdNOs derivatives were used as growth promoters in husbandry because of their strong antimicrobial activity [ 1 , 2 , 4 , 5 , 12 ]. However, up to now, the antimicrobial activity of QdNOs has mainly focused on the parent drugs and subsequent reactive oxygen species (ROS) and hydroxyl radicals from the bacterial metabolism of QdNOs [ 63 ]. It still remains undiscovered whether their metabolites have antibacterial activity and further study should be conducted to focus on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…As many studies suggested, QdNOs derivatives were used as growth promoters in husbandry because of their strong antimicrobial activity [ 1 , 2 , 4 , 5 , 12 ]. However, up to now, the antimicrobial activity of QdNOs has mainly focused on the parent drugs and subsequent reactive oxygen species (ROS) and hydroxyl radicals from the bacterial metabolism of QdNOs [ 63 ]. It still remains undiscovered whether their metabolites have antibacterial activity and further study should be conducted to focus on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The increase may be because of stress imposed on the bacteria by the extract, and in order to overcome the starvation, the bacteria produces more amount of ALP. Previous studies revealed that the ALP levels were increased in Clostridium perfringens and Brachyspira hyodysenteriae upon treatment with Quinoxaline 1,4-di- N -oxide derivatives compared to the non-treated groups [37]. Therefore, the observed significant increase in the ALP activities in the bacteria treated with M. minuta extract suggests an increase in the activities of the existing enzymes by the secondary metabolites.…”
Section: Resultsmentioning
confidence: 87%
“…According to our studies on steer rumen aliquots, quinoxaline dioxide 3 decreased k d by 15% with respect to UIR and with a concomitant increase in the lag time of 38%. Quinoxaline dioxides, such as carbadox, olaquindox, and mequindox [41,42], have been used to prevent bacterial infections and to improve animal growth due to their actions against gram-positive and gram-negative bacteria. However, currently they are banned due to health concerns over their (and their metabolites’) toxic effect of oxidative stress [43].…”
Section: Discussionmentioning
confidence: 99%